Protection Victims of Criminal Acts of Extortion and or Threats Through Social Media - Nugroho, Fajar Seto; Royani, Achmad; Mahardika, Salsabilah Panca (Universitas Islam Lamongan, 2025)
This research is motivated by the large number of people who commit unlawful acts in the form of extortion and/or threats using social media that can harm their users. The impact on victims affects physical, psychological, and material health. This research uses a Normative juridic research type with a Law approach and a concept approach. From the results of the study it can be concluded that the rules of criminal sanctions against perpetrators of extortion and/or threats are regulated in the Criminal Code, Law Number 31 of 2014 concerning Protection of Witnesses and Victims. While crimes through social media (Cybercrime) are regulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE).